PENGARUH THERMOMECHANICAL CONTROLLED PROCESSED (TMCP) TERHADAP PENGHALUSAN BUTIR DAN SIFAT MEKANIK PADUAN Cu-Zn 70/30[Influence of Thermomechanical Controlled Process on the Grain Size and Mechanical Properties of Cu-Zn 70/30] - Febriyanti, Eka (Jurnal Metalurgi, 2015)
Cu-Zn 70/30 alloys are widely used in many industrial products because of its superior characteristic and there is no substitute. To obtain Cu-Zn alloy material whose higher mechanical properties then it is done research in the form of new material or modification material from existing types of materials to appropriate with industry necessary. To minimize production cost, but it still produce good mechanical properties without the addition of alloy then it is developed grain refinement method which refers to Hall-Petch law. One of fabrication process alternative to optimize the mechanical properties of Cu-Zn 70/30 alloy namely thermo mechanical controlled processed (TMCP) method. TMCP is conducted to Cu-Zn 70/30 alloy in various deformation percentage at a level of 32.25%, 35.48%, and 38.7% at 500o C by double pass reversible method. For Cu-Zn 70/30 alloy the range suhu of TMCP is between 0.4-0.6 melting temperature or between 382°C-573°C. By metallographic examination is obtained decreasing of grain size of 29.53 μm at the edges and of 33.47 μm in the central part sample on 38.7% deformation degree. Meanwhile, by tensile testing can be seen that Cu-Zn 70/30 alloy material with 38.7% deformation degree produces ultimate tensile strength (UTS) value of 533 MPa, yield strength (YS) value of 435 MPa, and elongation percentage value of 10%. The hardness value obtained approximately around 155 HV to 146 HV in the edges to the middle part of material on 38.7% deformation degree.